Uji Validitas dan Reliabilitas Konstruk Dukungan Sosial Menggunakan SEM - Chintia Amanda; Hadi Suyono; A.M. Diponegoro (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
The purpose of this study is to test the validity and reliability of social support construction using SEM. The subjects of this study were 83 private high school students in Beringin Regency. The scale of this study uses a social support scale created by researchers developed from Smet (2004). The scale is arranged in the form of a Likert scale based on its aspects, totaling 24 statements with 4 answer choices. The scale was analyzed using SEM AMOS software version 24. The results of social studies provided to students helped improve the success of completing school